2008
DOI: 10.1177/1077559507306717
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcome and Criminal Offending by Youth With Sexual Behavior Problems

Abstract: Children and adolescents treated for general delinquency problems and rated by caregivers as having sexual behavior problems (N = 696) were compared with youth from the same sample with no sexual behavior problems (N = 1185). Treatment outcome through 12-months post-treatment follow-up and criminal offense rates through an average 48-month post-treatment follow-up were compared for both groups. It was hypothesized that youth with any sexual behavior problems (SBP) would improve significantly over time but woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
1
21
0
1
Order By: Relevance
“…Not only do JSOs appear to recidivate at much lower rates than adults sex offenders, but they have also shown to be more amenable to treatment and rehabilitation than adults (Chaffin, 2008;Craun & Kernsmith, 2006;Trivits & Reppucci, 2002). For example, several randomized control studies of multisystemic therapy (MST) have shown that MST has been found to significantly reduce problematic sexual behaviors and nonsexual reoffenses in JSOs, while similar treatments have not shown to be as effective in adults (Borduin, Henggler, Blaske, & Stein, 1990;Borduin, Schaeffer, & Heiblum, 2009;Letourneau, Chapman, & Schoenwald, 2008). Moreover, research has shown that JSOs offend against victims of both genders, while adult offenders may be more specialized in their victim gender preference (Finkelhor, Ormrod, & Chaffin, 2008).…”
Section: Characteristics Of Jsosmentioning
confidence: 96%
“…Not only do JSOs appear to recidivate at much lower rates than adults sex offenders, but they have also shown to be more amenable to treatment and rehabilitation than adults (Chaffin, 2008;Craun & Kernsmith, 2006;Trivits & Reppucci, 2002). For example, several randomized control studies of multisystemic therapy (MST) have shown that MST has been found to significantly reduce problematic sexual behaviors and nonsexual reoffenses in JSOs, while similar treatments have not shown to be as effective in adults (Borduin, Henggler, Blaske, & Stein, 1990;Borduin, Schaeffer, & Heiblum, 2009;Letourneau, Chapman, & Schoenwald, 2008). Moreover, research has shown that JSOs offend against victims of both genders, while adult offenders may be more specialized in their victim gender preference (Finkelhor, Ormrod, & Chaffin, 2008).…”
Section: Characteristics Of Jsosmentioning
confidence: 96%
“…Considerable work has been undertaken to improve delivery of assessment and intervention programmes, but there has been limited UK empirical research of a follow-up nature. This is in contrast to the US where there have been various attempts to establish recidivism rates and outcomes in 4 groups of treated and non-treated adolescent sexual offenders over the short and/or medium term (see, for example, Bonner et al, 1999;Letourneau et al, 2008). However, there has been little in-depth research, either in the UK or internationally, which has tried to establish the longer term developmental trajectories of children and young people with sexual behaviour problems after the involvement of child welfare or youth justice agencies has ceased and when the young people concerned have moved into young adulthood (Beckett, 2006;Masson and Hackett, 2003;Vizard, 2007).…”
Section: Introductionmentioning
confidence: 93%
“…If research focuses primarily on the seemingly small minority of young sexual abusers who re-offend (Letourneau et al, 2008) and, in the absence of any data on the majority of young sexual abusers who enter into adulthood without persistent sexual behaviour problems (Chaffin, 2008), policy may become skewed towards an unwarranted focus on risk. As a consequence, intervention responses on offer to individual young people may be unnecessarily intrusive and may fail to distinguish between those young abusers with extensive needs, as opposed to those who may need only a limited professional response.…”
Section: Introductionmentioning
confidence: 99%
“…Others, like Amand, Bard, and Silovsky (2008) and Letourneau et al (2008) mention the use of Multisystemic Therapy highly influenced by Cognitive Behavioural Therapy (CBT).…”
Section: Shb and Interventionsmentioning
confidence: 99%
“…Some information found provides definition, diagnosis and intervention about SHB such as the work of Friedrich (2008) or Letourneau, Chapman, and Schoenwald (2008). This material establishes a base to compare the most common interventions with DMP.…”
Section: Attachment Theory and Shbmentioning
confidence: 99%